Utilização de um modelo matemático-estatístico no estudo da radiação solar e temperatura média do ar - Sucharov, Elza Correia (1978)
The structural analysis and mathematical models used for evaluation and removal of the periodicity and dependence from the geophysical time series are reviewed, summarized and discussed. Records of daily global solar radiation and mean air temperature in Campinas - São Paulo, Estação Centro Experimental de Campinas (period 1965 to 1974) and KM 47 - Rio de Janeiro, Estação Ecologia Agrícola (period 1963 to 1973) are used as the basic research data. Fourier series are used to analyse the periodicity of the data. The linear autoregressive models are applied from the first to sixth order to describe the dependence of these series. Periodicities in serial correlation coefficients, rk,Ƭ, of the stochastic components are also analyzed. Independent stochastic components are obtained by removing the periodicity and dependence from the series. The probability distribution function normal, lognormal 3-parameters, gamma 3-parameters and double branch gamma are applied to fit the frequency distributions of the independent stochastic components.